Incidence, pathogenicity and diversity of Alternaria spp. associated with alternaria leaf spot of canola (Brassica napus) in Australia. (2nd November 2018) - Al‐Lami, H. F. D.; You, M. P.; Barbetti, M. J.
Abstract : Studies were undertaken to determine Alternaria spp. associated with leaf spot symptoms on canola ( Brassica napus ) in two cropping seasons (2015, 2016) across southern Australia. Major allergen Alt a1 and plasma membrane ATPase genes were used to identify Alternaria spp. In 2015, 112 isolates of seven Alternaria spp. were obtained, with A. metachromatica predominating. In 2016, 251 isolates of 12 Alternaria spp. were obtained, with A. infectoria predominating. Alternaria spp. isolates were morphologically and phylogenetically identified and studies to determine their pathogenicity on both B. napus (cv. Thunder TT) and B. juncea (cv. Dune) confirmed 10 species ( A. alternata, A. arborescens, A. brassicae, A. ethzedia, A. hordeicola, A. infectoria, A. japonica, A. malvae, A. metachromatica and A. tenuissima ) as pathogenic on both Brassica species. Alternaria ethzedia, A. hordeicola and A. malvae were recorded for the first time in Australia on any host and the record of A. arborescens was the first for New South Wales (NSW) and South Australia (SA). Other first records included A. infectoria on B. napus in NSW; A. japonica on B. napus in NSW and Western Australia (WA); A. metachromatica on any host in NSW, Victoria (VIC), WA and SA; and A. tenuissima on B. napus in NSW, SA and WA. It is evident that alternaria leaf spot on canola across southern Australia is not solely caused by A. brassicae, but that a range of other Alternaria spp. are also involved to varying degrees, depending upon the year and the geographic locality.